Pengaruh Kualitas Pelayanan, Keragaman Produk dan Lokasi Terhadap Kepuasan Pelanggan (Studi Kasus Pada Pelanggan Stove Syndicate Cafe di Semarang) - Loredah Paulina Nainggolan; Ari Pradhanawati (Universitas Diponegoro, 2016)
Along with the growth in the culinary business in Semarang, leading to higher levelcompetition faced by Stove Syndicate Cafe Semarang. The decline in sales and number of visitors inStove Syndicate Cafe Semarang indicate less than optimal customer satisfaction. This study aimed todetermine the effect of service quality, product diversity, and location take effect customer satisfactionStove Syndicate Cafe Semarang.This type of research is explanatory research design to data collection tool is questionnaire.This study used 100 respondents, consumer Stove Syndicate Cafe Semarang which has been apurchase more than second times . The sampling technique of this research is non probabilitysampling with accidental sampling approach. Test equipment instruments used are validity andreliability testing. Analysis of the data used is the correlation coefficient, determination coefficient,simple linear regression, t test, multiple linear regression, and F test.Based on the results of analysis show that in partial quality of service contributed influenceon customer satisfaction by 57,2%, the variable product diversity contributed influence on customersatisfaction by .52,5% and location variables contributing influence on customer satisfaction by51.1%. Simultaneously, quality of service, product diversity and location of contributing influence oncustomer satisfaction by 71.1%.The conclusion of this study indicate quality of service, product diversity, and locationpartially and simultaneously influence customer satisfaction Trans Stove Syndicate Cafe Semarang.Based on these results, the manager Stove Syndicate Cafe Semarang should be able to improve andcontinue to develop the quality of service to match the benefits of consumers, the diversity of existingproducts as well as continue to consistently innovate and improve the facilities associated with thelocation to be able to improve customer satisfaction stove Syndicate Cafe Semarang.